The greek and latin inscriptions in the governorate of ʿAjlun in north-west Jordan - Badr, Nabīl (Syria, 2016)
ʿAjlun Governorate, the smallest in Jordan, is located in the north west of the Hashemite Kingdom of Jordan. It has already delivered some Greek inscriptions, but as in other parts of the country, new inscriptions appear from time to time. Some newly discovered inscriptions were separately reported in various articles. Due to their importance, an overview may be useful. Among them, an exceptional bilingual Neohellenic and Arabic inscription was found in the city of ʿAjlun. This text which commemorates the building of a church in the 19th cent. is here published for the first time.